Capability of the cavalieri method for volume estimation of the dog testis - Murat Sırrı Akosman; Vural Özdemir (Eurasian Journal of Veterinary Sciences)
Aim: Aim of this research was to investigate the capability of Cavalieri principle (unbiased and efficient method using to volume measurement) for the in vitro estimation of the volume of the dog. Materials and Methods: Five male adult dog testes were used. First, testis volumes were measureament by water displacement method (Archimedes principle), then cavalieri method used to estimate the volume of same testis. Afterwards, the results of these methods were compared. Results: The mean volume of the left and right testis together was found 18.72 cm3 according to Archimedean principle and 18.25 cm3 according to Cavalieri principles. Statistical difference was not found (p<0.05). Conclusion: The direct volume measurement method “water displacement” could not be Performed on the small testis because of the “capillary effect”. However Cavalieri principle runs free from the shape and orientation of the material. The study showed that Cavalieri principle was capable to measure the testis volume.